Black men worshipping : intersecting anxieties of race, gender, and Christian embodiment - Boyd, Stacy C., 1973- (New York : Palgrave Macmillan, 2011)
"Black Men Worshipping analyzes the discursive spaces where Black masculinity is constructed, performed, and contested in American religion and culture. It judiciously considers the anxiety that emerges from Black male negotiations with these constructions, placing fictive literary and film narratives in conversation with the non-fictive narratives of controversial and popular religious personalities such as Donnie McClurkin and T.D. Jakes"--
Machine generated contents note: -- Messianic Masculinity: Killing Black Male Bodies in Uncle Tom's Cabin and The Green Mile * Christian Race Man: Bishop T.D. Jakes and the Search for Contemporary Christian Masculinity * Donnie McClurkin and the Tensions of Black Christian Sexuality * Father Stories and Hungry Sons in Ernest J. Gaines's In My Father's House.
Includes bibliographical references and index.
Keywords: African American men -- Religion; African Americans in literature; Religion in literature; African Americans in motion pictures; Religion in motion pictures; RELIGION / Christian Life / Men's Issues; RELIGION / Sexuality & Gender Studies; RELIGION / Christian Theology / General